2020
DOI: 10.3389/fmicb.2020.602124
|View full text |Cite
|
Sign up to set email alerts
|

Variation and Molecular Basis for Enhancement of Receptor Binding of H9N2 Avian Influenza Viruses in China Isolates

Abstract: Currently, H9N2 avian influenza viruses (H9N2 AIVs) globally circulate in poultry and have acquired some adaptation to mammals. However, it is not clear what the molecular basis is for the variation in receptor-binding features of the H9N2 AIVs. The receptor-binding features of 92 H9N2 AIVs prevalent in China during 1994–2017 were characterized through solid-phase ELISA assay and reverse genetics. H9N2 AIVs that circulated in this period mostly belonged to clade h9.4.2. Two increasing incidents occurred in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…The remaining H9N2 viruses tested that could bind to both avian- and human-type receptors carried the HA-155T and HA-226Q substitutions. The I155T mutation plays important roles in the binding of H9N2 virus to human-type receptors, but viruses with the 226Q mutation preferred avian-type receptors ( 39 ). Thus, we inferred that the two substitutions have opposite effects, leading to dual receptor-binding capacity of H9N2 viruses in wild birds.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining H9N2 viruses tested that could bind to both avian- and human-type receptors carried the HA-155T and HA-226Q substitutions. The I155T mutation plays important roles in the binding of H9N2 virus to human-type receptors, but viruses with the 226Q mutation preferred avian-type receptors ( 39 ). Thus, we inferred that the two substitutions have opposite effects, leading to dual receptor-binding capacity of H9N2 viruses in wild birds.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of Q227 in combination with either aspartic acid (D) or glutamic acid (E) at position 190 favors binding α2,6SAs receptors. Other changes such as A160D/N, Q156R, T205A, V245I, V216L, D208E, T212I, R1721 and S175N also enhance the human-like receptor binding in vitro [76,77]. The terminal sialic acid linkage is not the only factor that affects the binding of IAV HA to the host cell; other features such as the sialic acid structure (e.g., N-acetylneuraminic acid versus N-glycolylneuraminic acid) or length may also play a role (reviewed in [55]).…”
Section: Molecular Mechanisms Associated With Interspecies Transmission Of Iavsmentioning
confidence: 99%
“…Using miRNA-based interventions could be a breakthrough in creating efficient antiviral techniques to protect poultry populations as researchers continue to explore the functional features of these newly discovered miRNAs. A critical study of miRNA expression during H9N2 infection revealed important new information about the complex regulatory mechanisms in chicken dendritic cells ( 97 ). This study identified a total of 66 known and 36 novel differentially expressed miRNAs, shedding light on miRNA involvement in key signaling pathways such as endocytosis, p53, lysosome, RIG-I-like, and NOD-like receptor signaling pathways.…”
Section: Mirnas Involved In Poultry Diseasesmentioning
confidence: 99%